Hymnic narrative and the narratology of Greek hymns - Faulkner, Andrew, 1978-; Hodkinson, Owen, 1979- (Mnemosyne, Supplements, 2015)
Ancient Greek hymns traditionally include a narrative section describing episodes from the hymned deity's life. These narratives developed in parallel with epic and other narrative genres, and their study provides a different perspective on ancient Greek narrative. Within the hymn genre, the place and function of the narrative section changed over time and with different kinds of hymn (literary or cultic; religious, philosophical or magical). Hymnic Narrative and the Narratology of Greek Hymns traces developments in narrative in the hymn genre from the Homeric Hymns via Hellenistic and Imperial hymns to those in the Orphic tradition and in magical papyri, analysing them in narratological terms in order to place them in the wider context of ancient Greek narrative literature.